PENGARUH KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA INSPEKTORAT KABUPATEN PONOROGO - Wahyuningsih, Triana; Wahyudi, Amin; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
It has purpose to analyze the significance of organizational commitment and leadership style on work motivation as a mediating variable in the district inspectorate of Ponorogo. The benefits of practical research can be a consideration in management decision making in the future examinations and academically can increase knowledge, especially about the development of human resources. The sample is amounted to 39 respondents from a population of 39 civil servants with the calculation of the number of respondents using the technique taken from the entire population. The results of this study indicate that job satisfaction mediates the effect of organizational commitment on work motivation and job satisfaction mediates the influence of leadership style on civil servants work motivation in the district inspectorate of Ponorogo.